PAHs and PCBs in an Eastern Mediterranean megacity, Istanbul: Their spatial and temporal distributions, air-soil exchange and toxicological effects - Cetin, Banu; Ozturk, Fatma; Keles, Melek; Yurdakul, Sema (Elsevier Sci Ltd, 2017)
Istanbul, one of the mega cities in the world located between Asia and Europe, has suffered from severe air pollution problems due to rapid population growth, traffic and industry. Atmospheric levels of PAHs and PCBs were investigated in Istanbul at 22 sampling sites during four different sampling periods using PUF disk passive air samplers and spatial and temporal variations of these chemicals were determined. Soil samples were also taken at the air sampling sites. At all sites, the average ambient air Sigma(15)PAH and Sigma 41PCB concentrations were found as 85.6 +/- 68.3 ng m(-3) and 246 +/- 122 pg m(-3), respectively. Phenanthrene and anthracene were the predominant PAHs and low molecular weight congeners dominated the PCBs. The PAH concentrations were higher especially at urban sites close to highways. However, the PCBs showed moderately uniform spatial variations. Except four sites, the PAH concentrations were increased with decreasing temperatures during the sampling period, indicating the contributions of combustion sources for residential heating, while PCB concentrations were mostly increased with the temperature, probably due to enhanced volatilization at higher temperatures from their sources. The results of the Factor Analysis represented the impact of traffic, petroleum, coal/biomass and natural gas combustion and medical waste incineration plants on ambient air concentrations. A similar spatial distribution trend was observed in the soil samples. Fugacity ratio results indicated that the source/sink tendency of soil for PAHs and PCBs depends on their volatility and temperature; soil generally acts as a source for lighter PAHs and PCBs particularly in higher temperatures while atmospheric deposition is a main source for higher molecular weight compounds in local soils. Toxicological effect studies also revealed the severity of air and soil pollution especially in terms of PAHs in Istanbul. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Istanbul; PAHs; PCBs; Air-soil exchange; Toxicological effect